Evaluation of Container Yard Locations Using Discrete Simulation Method - Simarmata, Roberta; Sinulingga, Sukaria; Sembiring, Meilita Tryana (Jurnal Sistem Teknik Industri, 2024)
The loading and unloading process are activity of unloading goods from ships with cranes and then being brought and arranged in temporary warehouses. PT Prima Termina Petikemas is a subsidiary of Pelindo which is engaged in shipping container loading and unloading services. For customer satisfaction, one of the indicators of the company is the truck round time (TRT) which is 33 minutes. Currently, the external truck round time (TRT) for delivery is 43.62 minutes with waiting time by 16.32 minutes and truck round time (TRT) receiving is 37.72 minutes with waiting time by 9.75 minutes. The discrete event simulation method aims to evaluate the determination of effective alternative container yard locations to anticipate truck round time (TRT). For all improvement scenarios carried out, the selected scenario for delivery using 4 blocks and 6 units of Automated Rubber Gantry Tyred (1 unit reach stacker) and the percentage of each block load is 20%. This can reduce the truck round time (TRT) 27.37 minutes with the waiting time is to 8.93 minutes. For receiving activity using 5 blocks and 6 units of Automated Rubber Gantry Tyred (ARTG) and the percentage of each block load is 20%. The waiting time become 9.92 minutes and this reduces the truck round time (TRT) by 33.67 minutes.